Safer and stronger together? Effects of the agglomeration on nanopowders explosion. (March 2021) - Santandrea, Audrey; Pacault, Stéphanie; Bau, Sébastien; Oudart, Yohan; Vignes, Alexis; Perrin, Laurent; Dufaud, Olivier
Abstract: Among the factors influencing dust explosion, the particle size distribution (PSD) is both one of the most important and complex to consider. For instance, it is commonly accepted that the explosion sensitivity increases when the particle size decreases. Such an assertion may be questionable for nano-objects which easily agglomerate. However, agglomerates can be broken during the dispersion process. Correlating the explosion parameters to the actual PSD of a dust cloud at the moment of the ignition becomes then essential. The effects of the moisture content and sieving were investigated on a nanocellulose powder and the impact of a mechanical agglomeration was evaluated using a silicon coated by carbon powder. Each sample was characterized before and after dispersion using in situ laser particle size measurement and a fast mobility particle sizer, and explosion and minimum ignition energy tests were conducted respectively in a 20 L sphere and in a modified Hartmann tube. It was observed that drying and/or sieving the nanocellulose mainly led to variations in terms of ignition sensitivity but only slightly modified the explosion severity. In contrast, the mechanical agglomeration of the silicon coated by carbon led to a great decrease in terms of ignition sensitivity, with a minimum ignition energy varying from 5 mJ for the raw powder to more than 1J for the agglomerated samples. The maximum rate of pressure rise also decreased due to modifications in the reaction kinetics, inducing a transition from St2 class to St1 class when agglomerating the dust. Highlights: Explosion severity of nanopowders is slightly affected by brittle agglomerates. Explosion severity of nanopowders decreases if harder structures are present. Tests results depends on the agglomerates strength/dispersion stress ratio. Explosion moderation can be achieved by intentionally agglomerating nanopowders.